Regular Filter Cleaning Improves Bottom Line. Issue 11 (1st November 2013) - Cashion, Bob; Peters, Jason
Abstract : Filtration systems ‐ a utility's first line of defense against contamination ‐ are usually the most complex part of a water system. Regular filter maintenance extends equipment and facility life, decreases labor and repairs, and can reduce energy and chemical costs. This article is the first in a three‐part series about the importance of regular infrastructure cleaning and maintenance for equipment life and functionality, overall treatment performance, water quality, chemical requirements, and primary and secondary disinfection as well as disinfection by‐product control.